Avoiding ‘second victims’ in healthcare: what support do staff want for coping with patient safety incidents, what do they get and is it effective? A systematic review - Reema Harrison; Rebecca Lawton; Ruth Simms-Ellis; Raabia Sattar; Elizabeth Sweeting; Hannah Hartley; Matthew Morys-Edge (BMJ Open)
Objectives Incontrovertible evidence surrounds the need to support healthcare professionals after patient safety incidents (PSIs). However, what characterises effective organisational support is less clearly understood and defined. This review aims to determine what support healthcare professionals want for coping with PSIs, what support interventions/approaches are currently available and which have evidence for effectiveness.Design Systematic research review with narrative synthesis.Data sources Medline, Scopus, PubMed and Web of Science databases (from 2010 to mid-2021; updated December 2022), reference lists of eligible articles and Connected Papers software.Eligibility criteria for selecting studies Empirical studies (1) containing information about support frontline healthcare staff want before/after a PSI, OR addressing (2) support currently available, OR (3) the effectiveness of support to help prevent/alleviate consequences of a PSI. Study quality was appraised using the Quality Assessment for Diverse Studies tool.Results Ninety-nine studies were identified. Staff most wanted: peer support (n=28), practical support and guidance (n=27) and professional mental health support (n=21). They mostly received: peer support (n=46), managerial support (n=23) and some form of debrief (n=15). Reports of poor PSI support were common. Eleven studies examined intervention effectiveness. Evidence was positive for the effectiveness of preventive/preparatory interventions (n=3), but mixed for peer support programmes designed to alleviate harmful consequences after PSIs (n=8). Study quality varied.Conclusions Beyond peer support, organisational support for PSIs appears to be misaligned with staff desires. Gaps exist in providing preparatory/preventive interventions and practical support and guidance. Reliable effectiveness data are lacking. Very few studies incorporated comparison groups or randomisation; most used self-report measures. Despite inconclusive evidence, formal peer support programmes dominate. This review illustrates a critical need to fund robust PSI-related intervention effectiveness studies to provide organisations with the evidence they need to make informed decisions when building PSI support programmes.PROSPERO registration number CRD42022325796.